Peserta Didik dalam Pandangan Imam Al-Ghazali - Lubis, Ihsan Rinaldi; Suryani, Ira; Innayah, Azzira; Azzahra, Nazwa; Hafiza, Nur (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
In Imam Al-Ghazali's view, students have their own potentials to achieve moral and spiritual perfection and the role of educators is one that is very important and influential in helping them achieve this goal, educators basically must focus on the spiritual and moral development of students. In this journal, we describe Al-Ghazali's views on the potential of students, spiritual and moral development, as well as educational strategies that can be taken from the perspective of Imam Al-Ghazali. This research was conducted using qualitative methods, namely by analyzing and collecting and using literature studies. Learners are people who are experiencing a period of growth and development, especially physically and mentally. Imam Al-Ghazali's perspective on students and Islamic education is still relevant and can certainly be applied in the context of modern education. This can help educators to develop educational strategies that are holistic and focus on the spiritual and moral development of students. Keywords: Learners, Educators, Islamic Education